SWOT Analysis of Marketing Strategies in Increasing the Number of Students at LP3I Medan Polytechnic - Sihombing MSi, Iwan Kesuma; Alfasyimi, Hizbullah (Cattleya Darmaya Fortuna, 2023)
To find out internal factors (strengths and weaknesses) external factors (opportunities and threats) as considerations in determining policies for the Medan LP3I Polytechnic. This research uses qualitative methods to examine the condition of natural objects. This research uses descriptions from IFE internal environmental analysis research (Strengths and Weaknesses), EFE external environmental analysis (Opportunities and Threats), SWOT matrix, Quantitative Strategic Planning (QSPM) matrix analysis. The results of this research indicate that the internal environmental analysis of the Medan LP3I Polytechnic consists of Strength (S) and Weakness (W). Analysis of the external environment of the Medan LP3I Polytechnic consists of Opportunity (O) and Threat (T).